EDUKASI DAN SKRINING DEMENSIA DI MASJID AL JIHAD BANJARMASIN DALAM UPAYA PENCEGAHAN DEMENSIA PADA LANSIA - Fakhrurazy Fakhrurrazy; lily Runtuwene; Pagan Pambudi; Steven Steven; Muhammad Welly Dafif; Fitriah Handayani; Husnul Khatimah (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
Dementia is a brain disorder that causes a decline in memory, thinking ability, and behavior, which significantly affects the quality of life of older adults. According to data from the World Health Organization (WHO, 2023), more than 55 million people worldwide live with dementia, and this number continues to increase, particularly in low- and middle-income countries such as Indonesia. The low level of public awareness regarding the early symptoms of dementia has led to many undetected cases. This community service activity aimed to provide education about dementia to the congregation of Al Jihad Mosque in Banjarmasin and to conduct cognitive function screening using the Mini-Mental State Examination (MMSE) as an early detection effort. The activity was carried out on September 20, 2025, at Al Jihad Mosque, Banjarmasin, through educational sessions and dementia screening performed by a neurologist. A total of 49 participants took part in the activity, the majority aged 60–74 years (63.2%). The results showed that 97.9% of participants had normal cognitive function, while 2.0% exhibited a tendency toward cognitive impairment. These findings indicate the importance of routine screening among the elderly population, even when general cognitive function appears normal. This activity demonstrates that a faith-based community approach is effective in increasing awareness and promoting dementia prevention at the community level. Keywords: